E-047 Endovascular cerebellar artery sacrifice: clinical outcomes in 28 patients. (23rd July 2017) - Austin, M; Rimer, R; Chou, C; Wallace, A; Kamran, M; Moran, C; Cross, D; Osbun, J; Zipfel, G; Dacey, R; Kansagra, A
Abstract : Background: Endovascular treatment of lesions associated with the cerebellar arteries is ideally performed with preservation of cerebellar artery flow, but cerebellar artery sacrifice may sometimes be necessary. Clinical outcomes and complication rates of cerebellar artery sacrifice not well defined. Methods: We retrospectively reviewed cases of endovascular sacrifice of the superior cerebellar artery (SCA), posterior inferior cerebellar artery (PICA), and anterior inferior cerebellar artery (AICA) in patients with aneurysms, arteriovenous malformations (AVM), or tumors supplied by the corresponding artery. Baseline modified Rankin Scale (mRS) and pre-procedure acute intracranial hemorrhage hydrocephalus, and/or ventriculostomy were recorded along with diameter of the sacrificed cerebellar artery. Outcomes included new clinical neurological deficits, imaging evidence of cerebellar infarction, worsening hydrocephalus, new EVD placement, and craniectomy within 4 weeks of the procedure. Modified Rankin Scale at discharge and at 3 months was also recorded. Results: Of the 28 patients treated with endovascular cerebellar artery sacrifice, 22 had aneurysms, 5 had AVMs, and 1 had a tumor (hemangioblastoma) fed by the sacrificed cerebellar artery. Overall, 16 PICAs, 8 SCAs, and 4 AICAs were sacrificed. The mean vessel diameter was 1.45 mm. Twelve patients (42.9%) developed clinical neurological deficits within 4 weeks of the procedure that could be attributed to the occluded vessel. Of these patients, 8 developed imaging evidence of infarction in the corresponding arterial territory within 4 weeks of the procedure. Separately, there were 3 patients that developed imaging evidence of infarction without associated clinical neurological deficits. The mean vessel diameter of patients who developed imaging evidence of infarction was 1.2 mm, and the mean vessel diameter of patients who did not develop imaging evidence of infarction was 1.5 mm. Ten patients (35.7%) developed worsening hydrocephalus within 4 weeks of the procedure; 6 of these patients required placement of a new EVD. A single patient without worsening hydrocephalus required a new EVD electively after several unsuccessful attempts at weaning the indwelling contralateral EVD. Two patients required craniotomy within 4 weeks of the procedure, one which was planned pre-procedure and the other which was for evacuation of a new acute hematoma secondary to AVM hemorrhage. Six patients (21.4%) died prior to hospital discharge. Sixteen patients (57.1%) made a good recovery at 3 months (mRS ≤2). Mean angiographic follow-up period was 137.7 days (range 0–1169 days). Conclusions: Similar to open surgical cerebellar artery sacrifice, endovascular cerebellar artery sacrifice is associated with a high risk of infarction, hydrocephalus, and death. Disclosures: M. Austin: None. R. Rimer: None. C. Chou: None. A. Wallace: None. M. Kamran: None. C. Moran: 2; C; Medtronic, Microvention. D. Cross: None. J. Osbun: None. G. Zipfel: 1; C; NIH, AHA. R. Dacey: None. A. Kansagra: None.